Base-mediated denitrative C3-alkylation of quinoxaline derivatives - Pansare, Vaibhav Ramachandra; Barsu, Nagaraju (Organic & Biomolecular Chemistry, 2025)
We have developed a novel base-mediated method for the selective C3-alkylation of quinoxalin-2(1H)-one and N-protected quinoxalin-2(1H)-one using inexpensive, unactivated nitroalkanes. This approach tolerates a wide range of functional groups and supports the synthesis of various bioactive compounds. Gram-scale reactions demonstrate the scalability of the method. The proposed mechanism was validated by control experiments.